Development of Overgeneral Autobiographical Memory in Offspring of Depressed Mothers. Issue 1 (2nd January 2022) - Woody, Mary L.; Tsypes, Aliona; Burkhouse, Katie L.; Feurer, Cope; Champagne, Katelynn; Gibb, Brandon E.
ABSTRACT: Maternal depression increases the risk for offspring cognitive vulnerabilities, which may be a mechanism underlying the intergenerational transmission of depression. Little is known about how cognitive vulnerabilities, particularly memory biases, develop in the offspring of depressed mothers. Understanding the etiology of memory biases may lead to novel intervention targets. Therefore, the current study examined the prospective impact of maternal depression on the development of offspring overgeneral autobiographical memory (OGM; i.e., the tendency to recall less specific memories), a cognitive vulnerability implicated in the intergenerational transmission of depression. Participants were offspring (ages 8–14; 51% daughters, 81% Caucasian) of mothers with ( n = 129) or without ( n = 122) a history of major depressive disorder (MDD) during the offspring's life. Mothers and offspring completed assessments every 6 months for 2 years. Compared to offspring of never-depressed mothers, offspring of mothers with a history of MDD recalled less specific memories in response to negative, but not positive, cue words at the initial assessment, and this bias was maintained across the 2-year follow-up. For offspring of depressed, but not never-depressed, mothers, higher levels of maternal depressive symptoms at a given assessment predicted prospective decreases in the children's autobiographical memory specificity. Again, this finding was specific to negative, but not positive, cue words. These results suggest that maternal depression has both short- and long-term effects on the development of offspring OGM to negative cues, which may represent a malleable cognitive vulnerability for the intergenerational transmission of MDD that could be targeted for intervention.